Rachet Effects in Currency Substitution : An Application to the Kyrgyz Republic - Mongardini, Joannes; Mueller, Johannes (Washington, D.C. : International Monetary Fund, 1999)
Currency substitution is now a common issue in the design of monetary policy in most transition economies. This paper analyzes the persistence of this phenomenon in the Kyrgyz Republic by including a ratchet variable in the model specification. The main conclusion of the paper is that, while some degree of persistence is present in the allocation of bank deposit, currency substitution in the economy at large has not yet reached a point where reversing it would be difficult. In this regard, there is still room for monetary policy to influence currency allocation in the private sector.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet